Anne Mckeage: Former archivist and history of health and medicine librarian - Chen, Kevin; Lam, Ashley (The Meducator, 2018)
Anne McKeage was the former Archivist and History of Health and Medicine Librarian of the Health Sciences Library. We had the opportunity to sit down with Anne and discuss her work at McMaster. Curious to learn more about what goes on behind the scenes, we asked Anne to share with us her various experiences in gathering and organizing material for the History of Health and Medicine collection.